2015
DOI: 10.4321/s1575-06202015000100003
|View full text |Cite
|
Sign up to set email alerts
|

Salud laboral en un Centro Penitenciario de Chile: una mirada desde las políticas de Recursos Humanos

Abstract: This article examines the influence of human resources policies on occupational health variables, such as engagement and job satisfaction, with regard to Chilean prison employees. 80 workers at the Women's Prison of Iquique were evaluated and results show that 77% and 88 % have a moderate to high score in terms of engagement and job satisfaction respectively. The 24% variation in engagement of the workers studied can be explained by policies aimed at promoting personal interests, while 32% of the variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…Members of state security services present high levels of occupational stress, which results in progressive physical and mental deterioration, and is manifested in high levels of burnout 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of state security services present high levels of occupational stress, which results in progressive physical and mental deterioration, and is manifested in high levels of burnout 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Bajo este panorama, los miembros de organismos de fuerzas de seguridad del Estado presentan elevados indicadores de estrés en el trabajo, lo que se traduce en un progresivo deterioro físico y mental, manifestado en altos niveles del SBO 4 .…”
Section: Introductionunclassified
“…Surge entonces el denominado engagement o compromiso, caracterizado por el vigor (V) o la cantidad de energía y resiliencia, la dedicación (De) al trabajo con entusiasmo, el orgullo y la inspiración ante la tarea, y la absorción (A) o capacidad de concentración en el trabajo 10 . Güilgüiruca et al (2015) 11 mostraron que un 77% de los profesionales que utilizaban estrategias de afrontamiento de estrés cognitivo tienen un nivel de engagement entre moderado, y alto y un 88% de ellos presentan una satisfacción personal entre moderado y alto.…”
Section: Introductionunclassified
“…Güilgüiruca et al (2015) 11 showed that 77% of professionals who used coping strategies for cognitive stress have a moderate to high engagement level, and 88% presented moderate to high personal satisfaction.…”
Section: Introductionmentioning
confidence: 99%